Modelo de sustentabilidade econômica de empreendimentos comunitários de piscicultura a partir da organização de fatores de produção - Gomes, Francisco José (2022)
In rural areas, as there are higher rates of people living below the extreme poverty line than in the urban sector, public policies for rural productive inclusion, in the form of donations of materials and technical monitoring of management, have been implemented with the aim of to combat extreme poverty in these localities. What doesn’t always translate into income to producers for extended periods. In this sense, this work, as a result of survey carried out with fish farming associations, proposes an organizational model of factors aiming at the economic sustainability of the fish farming enterprise. The referred model was applied in a fish farmers association located in the city of Caxingó-PI, where it was verified that it brought significant improvements, mainly, in the increase of the income of the producers permanently, making it more predictable. Thus, it is interesting that organizational models of factors such as this be opotunized to other productive groups of pisciculture.